The Third Part of The Studies on Arche: The Principle of Law - Ebubekir Alan (Ankara Üniversitesi İlahiyat Fakültesi Dergisi)
In Ancient Greece, apart from skeptics and ethicists, practicing philosophy essentially meant engaging science, particularly physics and cosmology. The primary goal of this philosophy-science was to explain nature through three fundamental principles, which Aristotle identified as the material cause, the efficient cause, and the formal cause. Aristotle argued that these principles had been inadequately addressed by his predecessors, with the formal cause often overlooked. While Plato developed all three principles in Timaeus, Aristotle complicated the history of the studies on arche by ignoring Timaeus and claiming that Plato was not a physicist. This article focuses on the evolution of the third principle -the formal cause- within this framework, tracing its evolution from Thales to Plato.